MANAGEMENT DECISION-MAKING IN ACTIVITY OF PUBLIC AUTHORITIES: WORLD EXPERIENCE ANALYSIS - Tereshchenko D.A. (Pressing Problems of Public Administration, 2018)
The theoretical substantiation of objective prerequisites for management decision-making in thepublic authority systems of foreign countries is carried out. Рossible directions of adaptation of foreignexperience of work with information in the processes of development and adoption of managerialdecisions are proposed.